2008
DOI: 10.3357/asem.2130.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neck Muscle Strain When Wearing Helmet and NVG During Acceleration on a Trampoline

Abstract: Helmet weight alone had a large effect on muscular workload. The additional frontal weight of the NVG caused a further increase in the activity of cervical muscles that were already subjected to high strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…Many studies proofed, that NVG devices do not only allow pilots to enhance their visual capacity, but also come at the cost of increased mass leading to NVG-induced neck strain [21, 22]. Interestingly, in our study, helmet weight alone may have had an impact on neck pain and we refer to results of a study by Sovelius et al who reported, that helmet weight itself seems to induce more muscle strain than NVG [39]. Higher weight of the helmet has a more significant effect on cervical muscle loading then the lighter NVG, which alters the center of gravity [39].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Many studies proofed, that NVG devices do not only allow pilots to enhance their visual capacity, but also come at the cost of increased mass leading to NVG-induced neck strain [21, 22]. Interestingly, in our study, helmet weight alone may have had an impact on neck pain and we refer to results of a study by Sovelius et al who reported, that helmet weight itself seems to induce more muscle strain than NVG [39]. Higher weight of the helmet has a more significant effect on cervical muscle loading then the lighter NVG, which alters the center of gravity [39].…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, in our study, helmet weight alone may have had an impact on neck pain and we refer to results of a study by Sovelius et al who reported, that helmet weight itself seems to induce more muscle strain than NVG [39]. Higher weight of the helmet has a more significant effect on cervical muscle loading then the lighter NVG, which alters the center of gravity [39]. Moreover, neck pain prevalence might increase by using NVG more frequently, as Adam found a threshold value of 150 NVG hours, after which 90% of helicopter aircrew report neck pain [16].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The staff members were fully engaged in the treatment of patients, near all of the patients had only physical examination and recompression treatment and other examinations such as magnetic resonance imaging, computerized tomography or neurophysiologic techniques, which could be helpful in diagnosis and evaluation of the outcomes [24], [25], were nearly absent. No autopsy was performed for all the death cases.…”
Section: Discussionmentioning
confidence: 99%
“…Surface electromyography (sEMG) is commonly used to estimate muscular demands during mock or modified work tasks (Anton et al, 2001;Sood et al, 2007;Blackstone et al, 2008;Sheikhzadeh et al, 2008;Soveliues et al, 2008;Albayrak et al, 2007;Cort et al, 2006). It is an appealing method for occupational task assessment due to the quantity of information contained in the sEMG signal, and the ease of collecting sEMG in the field.…”
Section: Introductionmentioning
confidence: 99%